Is the smokers exposure to environmental tobacco smoke negligible? - Valerio Federico; Stella Anna; Piccardo Maria Teresa (BMC, 2010)
Abstract Background Very few studies have evaluated the adverse effect of passive smoking exposure among active smokers, probably due to the unproven assumption that the dose of toxic compounds that a smoker inhales by passive smoke is negligible compared to the dose inhaled by active smoke. Methods In a controlled situation of indoor active smoking, we compared daily benzo(a)pyrene (BaP) dose, estimated to be inhaled by smokers due to the mainstream (MS) of cigarettes they have smoked, to the measured environmental tobacco smoke (ETS) they inhaled in an indoor environment. For this aim, we re-examined our previous study on daily personal exposure to BaP of thirty newsagents, according to their smoking habits. Results Daily BaP dose due to indoor environmental contamination measured inside newsstands (traffic emission and ETS produced by smoker newsagents) was linearly correlated (p = 0.001 R2 = 0.62) with estimated BaP dose from MS of daily smoked cigarettes. In smoker subjects, the percentage of BaP daily dose due to ETS, in comparison to mainstream dose due to smoked cigarettes, was estimated with 95% confidence interval, between 14.6% and 23% for full flavour cigarettes and between 21% and 34% for full flavour light cigarettes. Conclusions During indoor smoking, ETS contribution to total BaP dose of the same smoker, may be not negligible. Therefore both active and passive smoking exposures should be considered in studies about health of active smokers.